Individual Educational Program for Slow Learner - Anggi Anggraeni (Psycho Holistic, 2022)
Slow learner is a condition where students have intellectual potential slightly below the average. Due to abilities below the average of children at their age, slow learner student’s ability in learning is slower than children at their age. With this condition, slow learner students need special education programs to optimize their potential so they can obtain learning outcomes as level as other student at their age group. This study discusses a design of individual education programs for slow learners students based on Reddy's theory, including providing motivation, giving individual attention, developing self-confidence, developing the habit of completing assignments well, and repeating the study by teacher or parent. If the programs can be done consistently by teachers and parents, the outcome will be effective in supporting the optimal learning for slow learners. This research based on literature review on books, journals, and articles from several databases such as Proquest, Google Scholar, and Pubmed from 2006 to 2021.